Sunday Worker (16 May 1926 : final edition) - Cook, A. J. (Arthur James) ; Horner, Arthur, 1894-1968 ; Pollitt, Marjorie ; Lansbury, George, 1859-1940 ; Mann, Tom, 1856-1941 ; Desai, M. G. ; Parker, Florence
16 May 1926